If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + y = -26 Solving 3x + y = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + y + -1y = -26 + -1y Combine like terms: y + -1y = 0 3x + 0 = -26 + -1y 3x = -26 + -1y Divide each side by '3'. x = -8.666666667 + -0.3333333333y Simplifying x = -8.666666667 + -0.3333333333y
| 3+2(4-x)=3x-7 | | 9(k)=36 | | -41=n-22 | | -8(a/8-2)=26 | | 2b-4=3(b+4) | | 12x-132=84 | | 50x^2-8=y | | 7x+18=x+10 | | x^3+4x^2-64x-256=x+24 | | 2x-3(3x-4)=4x-12 | | 21-v=16 | | 4+8=6(6) | | -77+7y=10x | | 4/5-4=3/1+12 | | 23x-5=-1.7x-5 | | -3(7n-6)=31-8n | | 3x-1=6x+20 | | u-15=1.5 | | 48=3k+12-k-4 | | -4=-4(m+5) | | y-5=x-0 | | 3(2-k)=-(4k+3) | | 14(h)=28 | | 9s+5-6s+2= | | 13-g=12 | | -45=5(2a/5+3) | | -2(n-5)=-6 | | 12+z=29 | | (2/3)2=(x)6 | | 1.8n=4 | | (16y-27)=(13y) | | j+-2=-22 |